177k views
4 votes
Please help me with how to solve this with steps.
y=−x+2
y=3x−4

1 Answer

4 votes

Answer:

Well you can solve this a lot of ways but this one is easy with substitution. The answer is (7/6,1/2)

Explanation:

Make one of the equations equal to x -

y=-x+2 can be converted to x=-y+2

Then substitute that into the second equation.

y=3(-y+2)-4

then simplify

y=-3y+6-4

y=-3y+2

add 3y to both sides to eliminate the -3y

4y=2

then simplify again.

y=1/2

Last step: plug in 1/2 as y in either equation and simplify to get x.

1/2=3x-4

You should get x=7/6

the answer is (7/6,1/2)

User Steve Waldman
by
5.3k points